1984
DOI: 10.1111/j.1528-1157.1984.tb04192.x
|View full text |Cite
|
Sign up to set email alerts
|

A Kindling‐like Effect Induced by Repeated Exposure to Heated Water in Rats

Abstract: Hyperthermia was induced in mature rats by immersing them in 20 cm of 45 degrees C water for 4 min. Rats were made hyperthermic once every 4 days for six exposures. A significant number had at least one convulsion by the third exposure. During the seventh exposure, 2 weeks after the sixth exposure, twice as many rats experienced convulsions. Two weeks later, four rats that had convulsed following exposure to heated water at an earlier time convulsed on exposure to a strobe light flashing at 25 Hz. The percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 28 publications
3
14
0
1
Order By: Relevance
“…96 (1-3). This result of ours has been found consistent with the study conducted by Klauenberg BJ and Sparber SB [5]. The EEG changes in pilocarpine-induced SE are defined as significant increase in theta rhythm and isolated horns in hippocampus, synchronization of hippocampal and cortical activities, and isolated electrographic seizures [30].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…96 (1-3). This result of ours has been found consistent with the study conducted by Klauenberg BJ and Sparber SB [5]. The EEG changes in pilocarpine-induced SE are defined as significant increase in theta rhythm and isolated horns in hippocampus, synchronization of hippocampal and cortical activities, and isolated electrographic seizures [30].…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, models of FS in the immature rat have been developed [5,6] and enhanced susceptibility to pilocarpine-induced seizures has been reported in these models [7]. Although pathophysiology of TLE is still unclear, one speculated mechanism is mutations of the genes that lead to defective sodium channels which stay open for too long, thus making the neurons hyper-excitable.…”
Section: Introductionmentioning
confidence: 99%
“…Although Klauenberg et al (27) and Ossenkopp et al (28) showed the shortening effect of MF on the seizure duration, Keskil et al (29) found no relation between them. In another study (30), using a similar method to that in our present study, it was shown that the seizure latency decreased but the seizure duration increased.…”
Section: Discussionmentioning
confidence: 97%
“…Hot water-induced seizures were described by Klauenberg and Sparber (1984). A 30 ϫ 60 ϫ 60 tank contained 15-cm-deep 45°C water, whose temperature was controlled by a heater.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate whether Scn1a mutant rats are susceptible to thermal stimuli, we used a hot water bath to induce FS (Klauenberg and Sparber, 1984)…”
Section: Susceptibility To Hismentioning
confidence: 99%